Destructive adsorption of methyl parathion over nanocrystalline MgO - Reddy, V. S.; RadheShyam, A.; Dwivedi, Reena; Gupta, R. K.; Chumbhale, Vilas R.; Prasad, R. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2005)
Destructive adsorption of methyl parathion (MP) has been investigated over few transition metal oxides and alkali earth metal oxides. Performance of alkaline earth oxides have been found to be better than transition metal oxides and best performance has been shown by aerogel method prepared nanocrystalline AP-MgO. The AP-MgO powder has been characterized by XRD, AFM and BET surface area measurements. Destructive adsorption of MP over AP-MgO has been compared with that of activated carbon. Both are found to adsorb methyl parathion effectively. An IR investigation of the surface of treated AP-MgO and activated carbon reveals that activated carbon adsorbs methyl parathion as such in the molecular form and AP-MgO adsorbs it destructively.

Vapour phase oxidation of acetophenone to benzoic acid over binary oxides of V and Mo - Chumbhale, Vilas R.; Paradhy, S. A.; Anilkumar, Mettu; Kadam, S. T.; Bokade, Vijay V. (Chemical Engineering Research and Design, 2005)
Test data for catalytic oxidation of acetophenone into benzoic acid performed at bench scale with V2O5-MoO3 catalyst in a continuous downflow metal reactor are presented. The process parameters such as temperature and flow rate influence the product distribution. The P2O5, B2O3 and Na2O when used as dopant on V2O5-MoO3 catalyst showed marked influence on activity and selectivity. An acidic catalyst like V2O5-MoO3-P2O5 favours formation of benzoic acid while a basic catalyst like V2O5-MoO3-Na2O favours formation of benzaldehyde. The addition of Na2O into V2O5-MoO3 binary oxides formed new phases (NaVMoO6 and Na2V2Mo3O15), which increased Arrhenius activation energy from 18.24 to 31.35 kcal mol(-1).
Keywords: acetophenone; activity; benzoic acid; carbon oxides; oxidation of acetophenone; selectivity

Vapour phase methylation of phenol over nanocrystalline ZnFe(2-x)A1(x)O(4) (x=0, 0.25, 0.5, 0.75 and 1.0) ferrospinel system - Reddy, Vanga S.; RadheShyam, A.; Dwivedi, Reena; Rai, A.; Anilkumar, Mettu; Chumbhale, Vilas R.; Aswar, A. S.; Prasad, R. (Indian Journal of Chemical Technology, 2006)
The alkylation ofphenol with methanol was carried out over ZnFe2-xAlxO4 (x = 0, 0.25, 0.5, 0.75 and 1.0) type spinel systems in a Fixed bed, down flow reactor. The influence of Surface acidity, cation distribution in the spinel lattice and various reaction parameters are discussed. A maximum yield of 70.9 and 22.9% with selectivity of 73.5 and 23.3% was obtained for 2,6-xylenol and o-cresol respectively, giving a total ortho selectivity of: 96.8% over ZnFeAlO4 at 350 degrees C, methanol to phenol molar ratio of 5 and WHSV of 0.6 h(-1). Catalyst characterization was made by XRD, Mossbauer spectroscopy, ammonia desorption and BET surface area measurements. Mossbauer spectroscopy reveals isomorphic substitution or Fe 3 by smaller A 13, into the octahedral sites leading to lattice distortion, Unsymmetrical charge distribution and charge transfer from iron to oxygen making it more basic and proton attracting. This helps vertical adsorption ofphenol and formation of 2.6-xylenol. It has been concluded that catalyst acidity plays major role in the reaction as compared to surface area.
Keywords: consecutive methylation; ferrospinels; vertical and horizontal adsorption

Applications of zeolites in industrial and other purposes - Chumbhale, Vilas R. (Research Journal of Chemistry and Environment, 2010)

Gas-phase oxidant-free oxidation of cyclohexanol over V2O5-MoO3-M2O (M = Na, K, Cs) catalysts - Vyawahare, Y. K.; Chumbhale, Vilas R.; Pardhy, S. A.; Samuel, V.; Aswar, A. S. (Indian Journal of Chemical Technology, 2010)
Oxidant-free oxidation (dehydrogenation) of cyclohexanol is carried out in a down-flow integral laboratory scale reactor using different alkali doped catalysts. The effect of reaction temperature, contact time (W/F) and doping of alkali metals is studied to check its effect on nature of prominent products of the reaction (cyclohexanone and cyclohexene). At lower temperature the cyclohexanone prevails whereas at higher temperature cyclohexene is observed in prominence. Acid-modified catalysts (with boron and phosphorous) facilitated cyclohexene selectivity whereas alkali modified catalysts facilitated cyclohexanone selectivity. Calcination of sodium modified catalyst at different temperatures under static condition affect characteristic phase intensity and cyclohexanone selectivity. XRD investigation showed formation of different inorganic phases as the characteristic of dopant. Cesium modified catalyst showed better dehydrogenation activity.
Keywords: Cyclohexanol; dehydration; Dehydrogenation; Electronegativity; V2O5-MoO3

Kinetics studies and mechanism evolution of the epoxidation of styrene over nanoporous Au doped TS-1 - Saxena, Samidha; Dwivedi, Reena; Bhadauria, Sheenu; Chumbhale, Vilas R.; Prasad, Rajendra (Polish Journal of Chemical Technology, 2010)
{A kinetic investigation of the slurry phase epoxidation of styrene with hydrogen peroxide has been carried out, for the first time, over nanoporous Au doped TS-1 catalyst, in a batch reactor, in the temperature range of 313-333 K. It was found that product selectivity and the rate of reaction are greatly influenced by concentrations of styrene and hydrogen peroxide. Kinetics studies reveal that the mechanism of the reaction is of the ``Redox'' type. The rate equation
Keywords: Au/TS-1; epoxidation; kinetics; styrene; Styrene oxide

Alkylation of benzene to cumene over mor zeolite catalysts - Vyawahare, Yogesh K.; Chumbhale, Vilas R.; Aswar, Anand S. (Revue Roumaine De Chimie, 2012)
The vapor phase alkylation of benzene to cumene (isopropyl benzene) is studied over MOR (mordenite) type zeolite at different process parameters. The reaction was also studied by adopting different methodologies (pyridine poisoning, passing of moist propylene, alkali dominant mordenite, use of coked catalyst and metal impregnated zeolite) to check the nature of product distribution and the extent of activity and selectivity to alkylated product IPB, DIPB (isopropyl benzene and diisopropyl benzene) and n-PB (n-propyl benzene). It is revealed that the adoption of different methodologies affects the activity and selectivity significantly by suppressing of alkylation / isomerisation reactions.
Keywords: Alkylation; cumene; isopropanol; MOR zeolite; propylene